The Effect of Murottal Al-Quran Therapy on Anxiety Level of Chronic Kidney Disease Patients Undergoing Hemodialysis - Tri Hapsari Retno Agustiyowati; Diana Ros Endah; Tri Antika Rizki Kusuma Putri (STIKep PPNI Jawa Barat, 2022)
Aims: Chronic kidney disease patients undergoing hemodialysis have several effects on dialysis, one of which is anxiety. According to several studies, anxiety can be overcome by murottal al-Qur'an music therapy. Listening to the Qur'an can have a calming effect on the body, because of the elements of autosuggestion meditation and relaxation. This relaxation will bring a positive perception that can stimulate the hypothalamus to secrete endorphins released by the pituitary gland and central nervous system to increase feelings of relaxation and distract from fear, anxiety, and tension. Objective: to determine the effect of murottal al-Qur'an therapy on anxiety levels in chronic kidney disease patients undergoing hemodialysis. Methods: This research is a quantitative study with a Quasy Experimental research design. One group pretest-posttest with a total sample of 34 respondents. The instrument used in this study is the Zung Self Anxiety Rating Scale (ZSAS) instrument, which is an assessment of anxiety in patients designed by William WK Zung which consists of 20 statements. Results: Characteristics of respondents who took part in this study were aged 32-60 years, most of the respondents who took part in this study were aged 46-55 years as many as 17 respondents (50.0%), male (64.7%) , the length of time undergoing hemodialysis in the range of 7-44 months, most of the respondents underwent hemodialysis for a period of 6-12 months as many as 9 respondents (29.3%). The characteristic value of the ZSAS questionnaire, the largest value in the pre-test is at number 20 with a score of 126 while the largest value in the post-test is at number 5 with a score of 112. From the results of the Paired Simple T-test analysis, the p-value = 0.000, which means there is a significant relationship between murottal al-qur'an therapy and the anxiety level of chronic kidney disease patients undergoing hemodialysis. Conclusion: the study showed that there was a significant effect on anxiety after being given murottal al-qur'an therapy from the Ar-Rahman surah. The murottal therapy expected to be implemented by nurses to reduce the anxiety level of chronic kidney disease patients undergoing hemodialysis.